Performance of edible cactus (Opuntiaficus-indica) in saline environments - GAJENDER, GAJENDER; SINGH, GURBACHAN; DAGAR, J C; LAL, KHAJANCHI; YADAV, R K (The Indian Journal of Agricultural Sciences, 2014)
Edible cactus [Opuntiaficus-indica (L.) Mill.] has been used as fruit, vegetable, forage and wide range of commercial purposes in arid regions. It has high efficiency to produce biomass per unit water use due to specialized photosynthetic mechanism. Owing to its tolerance to low input and adverse conditions, it has ample scope for introduction and cultivation in arid and saline parts of world. A field experiment was conducted to standardise planting techniques and irrigation requirements of cactus at Hisar (Haryana) during 2008-2010. Cactus clones 1270, 1271, 1280 and 1287 were planted on ridges, flat beds and furrows with no irrigation, irrigations at one month and two months interval using saline ground water. Raised bed plantations resulted in better survival and plant height. The survival was higher without irrigation but the plant height was higher with monthly irrigation. Clone 1270 sprouted earliest and highest survival was recorded in clone 1271. To assess salinity and alkalinity tolerance, clone 1280, was planted at Karnal. Three soil salinity (ECe) levels and four pH levels were maintained along with no fertilizer, NPK and FYM. This clone was found to tolerate moderate salinity (52 mM) but sensitive to pH and had negligible growth at pH 9.8. Application of NPK and FYM helped in mitigating the effects of salt stress. Raised bed planting was advantageous and once established, Opuntia can sustain saline groundwater irrigation for optimum growth and production.